The ALPINE-ALMA [C ii] survey: a triple merger at z ∼ 4.56. (7th October 2019) - Jones, G C; Béthermin, M; Fudamoto, Y; Ginolfi, M; Capak, P; Cassata, P; Faisst, A; Le Fèvre, O; Schaerer, D; Silverman, J D; Yan, Lin; Bardelli, S; et al.
ABSTRACT: We report the detection of [C ii ] λ158 $\mu$ m emission from a system of three closely separated sources in the Cosmic Evolution Survey (COSMOS) field at z ∼ 4.56, as part of the Atacama Large Millimeter/submillimeter Array (ALMA) Large Program to INvestigate C ii at Early times (ALPINE). The two most luminous sources are closely associated, both spatially (1.6 arcsec ∼ 11 kpc) and in velocity (∼100 km s −1 ), while the third source is slightly more distant (2.8 arcsec ∼ 18 kpc, ∼300 km s −1 ). The second most luminous source features a slight velocity gradient, while no significant velocity gradient is seen in the other two sources. Using the observed [C ii ] luminosities, we derive a total log$_{10}(\rm SFR_{[C\, {\small II}]}\, [M_{\odot }\, yr^{-1}])=2.8\pm 0.2$, which may be split into contributions of 59, 31, and 10 per cent from the central, east, and west sources, respectively. Comparison of these [C ii ] detections to recent zoom-in cosmological simulations suggests an ongoing major merger. We are thus witnessing a system in a major phase of mass build-up by merging, including an ongoing major merger and an upcoming minor merger, which is expected to end up in a single massive galaxy by z ∼ 2.5.